2020
DOI: 10.1097/ans.0000000000000283
|View full text |Cite
|
Sign up to set email alerts
|

Epistemic Injustice

Abstract: See the video here https://www.youtube.com/watch?v=z8zLM_hIw7Y. The event was honoring the World Art Day, 15 April (2012) in Sweden. 2 Reminiscent of 19 th century blackface minstrel shows, this cake depicts dark black body with white eyes, disproportionately large open mouth, large white teeth framed by blood red lips. 3 The event was to celebrate the Swedish Art Day: 7 th April. 4 National Afro-Swedish Association (Afrosvenskarnas riksförbund). A Brussels-based antiracism group has condemned Swedish culture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 170 publications
(340 reference statements)
0
1
0
Order By: Relevance
“…Indeed, (Ashcroft et al, 2021) found that patients accessing care for depression and anxiety felt the need to adopt “medical jargon” (p. 1176) in order to gain the respect of providers. Underlying these social dynamics is a collective consensus around who “controls the perception of what counts as a problem in the first place?” and “it is often not the patient—especially if they have low social capital” (Narruhn & Clark, 2020, p. 89). Indeed, these taken‐for‐granted dynamics that epistemically mediate these relations are systemic in nature, embedded within healthcare systems, and not just existing in individual cases (Kidd & Carel, 2017).…”
Section: Epistemic Injustice (Ei) and Youth Mental Health Researchmentioning
confidence: 99%
“…Indeed, (Ashcroft et al, 2021) found that patients accessing care for depression and anxiety felt the need to adopt “medical jargon” (p. 1176) in order to gain the respect of providers. Underlying these social dynamics is a collective consensus around who “controls the perception of what counts as a problem in the first place?” and “it is often not the patient—especially if they have low social capital” (Narruhn & Clark, 2020, p. 89). Indeed, these taken‐for‐granted dynamics that epistemically mediate these relations are systemic in nature, embedded within healthcare systems, and not just existing in individual cases (Kidd & Carel, 2017).…”
Section: Epistemic Injustice (Ei) and Youth Mental Health Researchmentioning
confidence: 99%